2008
DOI: 10.1590/s0100-29452008000300023
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação genética de indivíduos e progênies de cupuaçuzeiro no estado do Pará e estimativas de parâmetros genéticos

Abstract: RESUMO-O presente trabalho relata a avaliação genotípica de progênies de cupuaçuzeiro, no Estado do Pará, para os caracteres número de frutos (NF) em quatro safras, intensidade de ocorrência de vassoura-de-bruxa na inflorescência (VBI) e nos frutos (VBF), e peso de vassoura-de-bruxa (PVB). Apresenta também estimativas de parâmetros genéticos que permitem inferir sobre o controle genético e nível de variabilidade genética presente no material avaliado. Todos os caracteres apresentaram considerável variabilidade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 1 publication
(2 reference statements)
0
12
1
7
Order By: Relevance
“…The obtained values were lower than those reported by Maia et al (2011b) in cupuaçu progenies for the same variables under study. In studies on progenies, Alves & Resende (2008) reported coefficients of genetic variation ranging from 27% to 88% at progeny level, and from 38% to 123% at individual level, which evidences excellent selection possibilities in the studied population. Whereas for the trait witches'-broom resistance, Alves et al (2009) obtained CVgi% values ranging from 5% to 41%.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…The obtained values were lower than those reported by Maia et al (2011b) in cupuaçu progenies for the same variables under study. In studies on progenies, Alves & Resende (2008) reported coefficients of genetic variation ranging from 27% to 88% at progeny level, and from 38% to 123% at individual level, which evidences excellent selection possibilities in the studied population. Whereas for the trait witches'-broom resistance, Alves et al (2009) obtained CVgi% values ranging from 5% to 41%.…”
Section: Resultsmentioning
confidence: 67%
“…In studies with progenies, Maia et al (2011b) described mean heritability values ranging between 25% and 67%, and individual narrow-sense heritability values ranging between 16% and 64% for the variables of characterization and fruit production of cupuaçu. Alves & Resende (2008) reported individual narrow-sense heritability values, in one growing season, ranging from 25 to 54%.…”
Section: Resultsmentioning
confidence: 99%
“…Asexual propagation, it was assumed that genetic control could be of a higher level with respect to sexually propagated material. This was verified in the case of copoazu (Theobroma grandiflorum) by Alves and Resende (2008) who verified a much higher genetic gain through clonal propagation compared to sexual propagation. It should be noted that the agronomic management was minimal in the plot under study and that it is a floodable area.…”
Section: Discussionmentioning
confidence: 80%
“…The reference to "average fruit weight" showed high regularity in the superiority of individuals from one cycle to another, with only three crops being necessary to predict values with a certainty level above 90%. Alves and Resende (2008) in Para-Brazil, for four harvests of Copoazu (Theobroma grandiflorum) found for individual fruit number repetitions (r) of 35%. The individual heritability of the number of fruits in 4 harvests, increased to 48%, favoring a selective precision of 70%.…”
Section: Discussionmentioning
confidence: 99%
“…Some recent articles (COSTA et al, 2008a;COSTA et al, 2008b;ALVES & RESENDE, 2008;ASSIS et al, 2008;PETEK et al, 2008;CARGNELUTTI FILHO & STORCK, 2009) refer to the selective precision statistic as a measurement of precision or experimental quality for the selection of genotypes.…”
Section: Introductionmentioning
confidence: 99%